Growth Parameters and Survivability of Saccharomyces boulardii for Probiotic Alcoholic Beverages Development - de Paula, Breno Pereira; Chávez, Davy William Hidalgo; Lemos Junior, Wilson José Fernandes; Guerra, André Fioravante; Corrêa, Mariana Ferreira Dutra; Pereira, Karen Signori; Coelho, Maria Alice Zarur (Frontiers in Microbiology, 2019)
The aim of this research was to optimize the growth parameters (pH, ethanol tolerance, initial cell concentration and temperature) for Saccharomyces boulardii and its tolerance to in vitro gastrointestinal conditions for probiotic alcoholic beverage development. Placket-Burman screening was used to select only statistically significant variables, and the polynomial mathematical model for yeast growth was obtained by central composite rotatable design. Confirmation experiments to determine the kinetic parameters for yeast growth were carried out by controlling the temperature and pH. Soon after, the survivability of yeast was tested under in vitro conditions mimicking the human upper gastrointestinal transit. Saccharomyces boulardii had suitable resistance to alcohol and gastrointestinal conditions for probiotic alcoholic beverage development.